Improving thermodynamic performance of refrigerator condenser using nanoparticles - Милованов, Валерий Иванович; Балашов, Дмитрий Александрович (Technology audit and production reserves, 2016)
Data about the effect of nanoadditives on the work of heat exchangers of small refrigerator in the literature are practically absent. It is difficult to find technical solutions aimed at improving the efficiency of small refrigerators. Thus, work on further research of small refrigerators with nanofluids as the working body becomes actual. Reduce the electricity consumption of refrigerator is possible by improving the efficiency of heat exchange systems. New heat transfer fluids with better thermodynamic characteristics are one option to improve heat transfer. An important achievement in the study of heat transfer fluids is the use of a colloidal mixture of primary coolant liquid and metal particles with the size of 1-100 nm. Initial versions of colloidal solutions, such as microfluids, resulted in formation of a precipitate, causing erosion of the friction surfaces of metal parts. Nanofluids are unconnected monoparticles located in the base fluid. Their use can increase the heat transfer more than 50% in actual refrigerators of heat exchangers even when the relative amount of nanoparticles is less than 0,3 %. The paper compares the parameters of the condenser of small refrigerating machine using pure refrigerant and nanoparticle additives. Further, a comparison of theoretical calculation and experimental data of the condenser are conducted. The experiment revealed that the use of nanoadditives increases the heat transfer coefficient by 16 % in comparison with the pure refrigerant, which makes them promising means of improving the efficiency of the refrigerator without requiring structural changes.